LABDANO DITERPENE DERIVATIVES AND THEIR POTENTIAL CYTOTOXIC ACTIVITIES - Heleno, Vladimir Constantino Gomes; Resende, Ana Laura Matias; da Silva Gomes, Jadson; dos Santos, Raquel Alves; da Silva, Jonas Joaquim Mangabeira; Paulino, Julia Mirian (Seven Editora, 2025)
Esterifications were performed with labdane-type diterpenes, initially with polyalctic acid using alkyl and aryl halides as reagents, yielding five semi-synthetic derivatives, three of which presented yields greater than 70%. The derivatives were subjected to 1H and 13C NMR and identified by comparison with the starting material. Ent-copalic acid and ent-β-acetoxycopalic acid were reisolated from copaiba oleoresin (a commercial sample) and identified by 1H NMR in comparison with the literature. For ent-copalic acid, a reaction study was performed to improve yields. Both were subjected to esterifications using the DCC/DMAP system, yielding three new semi-synthetic derivatives. After this, all derivatives and their respective starting materials were subjected to cytotoxic evaluation against a breast tumor cell line and against normal mammary gland cells. The results were very interesting, with the halogenated derivatives in the polyhaltic group showing great promise, with one of them showing similar toxicity to the positive control (activity parameter for the assay). For the copaltic group, the results showed that the active molecule fusion technique can lead to excellent results. DOI: https://doi.org/10.56238/sevened2025.029-082